MDCube: A High Performance Network Structure for Modular Data Center Interconnection - Wu, Haitao; Lu, Guohan; Li, Dan; Guo, Chuanxiong; Zhang, Yongguang (ACM SIGCOMM CoNEXT, 2009)
Shipping-container-based data centers have been introduced as building blocks for constructing mega-data centers. However, it is a challenge on how to interconnect those containers together with reasonable cost and cabling complexity, due to the fact that a mega-data center can have hundreds or even thousands of containers and the aggregate bandwidth among containers can easily reach tera-bit per second. As a new inner-container server-centric network architecture, BCube interconnects thousands of servers inside a container and provides high bandwidth support for typical traffic patterns. It naturally serves as a building block for mega-data center. In this paper, we propose MDCube, a high performance interconnection structure to scale BCube-based containers to mega-data centers. MDCube uses the high-speed uplink interfaces of the commodity switches in BCube containers to build the inter-container structure, reducing the cabling complexity greatly. MDCube puts its inter- and inner-container routing intelligences solely into servers to handle load-balance and fault-tolerance, thus directly leverages commodity instead of high-end switches to scale. Through analysis, we prove that MDCube has low diameter and high capacity. Both simulations and experiments in our testbed demonstrate the fault-tolerance and high network capacity of MDCube.